Evaluating Educational Tool for Young Learners: Formative Assessment Techniques in the Grade 2 English Textbook "My Next Words" - Hakim, Putri Kamalia; Dafitri, Fela; Rahmawati, Maya (Jambura Journal of English Teaching and Literature, 2025)
This study investigates formative assessment techniques within the grade 2 English textbook “My Next Words”, focusing on their effectiveness in supporting young learners’ language development. Employing a descriptive evaluative methodology, this research analyzes three representative chapters from the textbook using a structured analytical framework influenced by foundational educational theories from Wortham (204), Boyd (2020), and Gullo (2004). The analysis is centered on several key aspects of formative assessment: task design and effectiveness, task duration and adaptability, task presentation and support, feedback and reinforcement, and repetition and practice. Data were collected through a detailed evaluation checklist applied to selected textbook chapters, with a binary rating system quantifying the presence of effective formative assessment strategies. The findings reveal that while the textbook effectively utilizes engaging and developmentally appropriate activities, there are notable gaps in providing structured progress markers, authentic language, personalized learning experiences, and varied feedback mechanisms. These gaps suggest opportunities for enhancing the textbook’s instructional design to better meet the developmental needs and learning styles of young learners. The implications of this study extend to curriculum developers and educational practitioners, emphasizing the need for textbooks that not only engage young learners but also systematically track and support their language learning progress.